PENGATURAN HUKUM DALAM KEADAAN DARURAT DIMASA PANDEMI COVID-19 - Susetio, Wasis; Azis, Rizka Amelia; Nurhayani, Nurhayani; Hikmawati, Elok (Jurnal Pengabdian Masyarakat AbdiMas, 2021)
It has been almost 2 years since the world, and especially Indonesia, has experienced a corona virus pandemic (Covid19). At the beginning of the pandemic, President Jokowi issued Presidential Decree Number 11 of 2020 concerning the Determination of the Public Health Emergency of Corona Virus Disease 2019 (COVID !()). Thus, the emergency status was based on Law Number 6 of 2018 concerning Health Quarantine on March 31 2O2O which simultaneously the President issued Government Regulation in Lieu of Law (PERPU) number 1 of 2020 on the same date. These two legal products were followed by other laws and regulations such as Government Regulation Number 21 of 2020 concerning Large-Scale Social Restrictions (PSBB) in the Context of Accelerating the Handling of Corona Virus Disease 2019. In its implementation, PSBB which is a nomenclature or normative term in Article 1 number 11 of the Health Quarantine Law becomes a reference and legal basis for implementing pandemic regulations in the regions. January 6th i 2021, a provision is issued regarding the Enforcement of Restrictions on Community Activities (PPKM) based on the Instruction of the Minister of Home Affairs Number 1 of 2021. This is of course a question, considering then, this Inmendagri became a kind of basis for the implementation of various PPKM rules, both those with a Micro nomenclature, as well as the issuance Emergency PPKM based on Inmendagri number 15 of 2021 concerning emergency PPKM. The problem is, how can a regulation such as a Ministerial Instruction be used as a legal basis with sanctions.What is the legal basis for the issuance of the Ministerial Instruction based on Law Number 12 of 2011 concerning the Establishment of Legislation Keywords : Emergency, PSBB, PPKM